KUB Chickens Leukocyte Number And Haemoglobin Level Affected by Garlic Juice Supplementation - Yossie Yumiati; Heri Dwi Putranto; Neval One Maghreta Putra; Nurmeiliasari Nurmeiliasari; Muhammad Dani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze the effects of four doses of garlic juice supplemented in drinking water on the leukocyte (white blood cell) count and hemoglobin levels of KUB chickens. Methodology: The experimental design used was Completely Randomized Design (CRD) consisting of 5 garlic juice supplementation doses treatments with 4 replications. The treatments consisted of G0 (control, 0 ml garlic juice in 1,000 ml drinking water), G1 (10 ml garlic juice in 1,000 ml drinking water), G2 (20 ml garlic juice in 1,000 ml drinking water), G3 (30 ml garlic juice in 1,000 ml drinking water), and G4 (40 ml garlic juice in 1,000 ml drinking water). Supplementation was carried out for 8 weeks. The variables measured were the number of leukocytes and hemoglobin levels. Datas were analyzed using analysis of variance and continued by Duncan Multiple Range Test. Findings: Garlic juice as a herbal supplement can be given up to 40 ml. Novelty: Strengthen the effectiveness of garlic juice as herbal supplementation. Originality: This study would be the first scientific research on herbal supplementation of garlic in liquid form (juice). Conclusion: Supplementation of garlic juice up to dose of 40 ml in 1,000 ml drinking water has not been able to affect the number of leukocytes and hemoglobin levels in blood of KUB chickens. Type of Paper: research article.